Analisis Persaingan Ekspor Tekstil Indonesia Dengan Vietnam - Agatha Merih Trulin Ginting; Gracia Natalie Riswinanda; Rachel Theresia Novelita Hutabarat; Rinandita Wikansari (Universitas Kristen Indonesia Toraja, 2024)
In the international trade market, there is intense competition between Indonesia and Vietnam in textile exports. This study examines the dynamics of this competition with a concentrate on the elements that affect the outcome of both countries in exporting textiles to the world market. The focus of the analysis is on competitive advantage, business strategy and the economic impact of the country. Using a comprehensive research method, the journal identifies that production costs, product innovation and marketing strategies are key factors in textile export competition. Comparative advantage in this case plays an important role in shaping each country's position in the international market. The analysis also covers both countries' responses to global market dynamics, trade policy changes and other challenges affecting the textile industry. By understanding these factors, this journal provides policy recommendations that can improve the competitiveness and export status of Indonesian and Vietnamese textiles. The results of this study make an important contribution to understanding the complexity of textile export competition at the international level and provide a foundation for political strategies that can support both countries' sustainable growth in this sector. The analysis also covers both countries' responses to global market dynamics, trade policy changes and other challenges affecting the textile industry. The results this research offer an examination of two countries' responses to global market dynamics, trade policy changes and other challenges affecting the textile industry.